EFFECT OF THE JIGSAW LEARNING MODE ON THE RESULTS OF HIGH SCHOOL GEOGRAPHY LEARNING - Meta Neyla (Journal Learning Geography, 2021)
The present study tries to find the significant different of learning result of geography subject between students who are learned with jigsaw learning model and those who are learned with teachers' explanation and discussion model. The hypothesis for the study is there is a significant different of the learning result of students who are learned geography subject with jigsaw learning model and those who are learned with teachers' explanation and discussion model. The present study applied quasi experimental approach withNon Equivalent Control Group Design. The dependent variable is learning result and its independent variable is the jigsaw learning model. As the instrument essay test was used to test the students' learning result. The results in the form of data, later, were analyzed by using t-test with SPSS 16.0 for Windows. The average gain score of the students' learning result from the experiment group is higher than in the control group, 4 , 75 and 2.60. The result data of t-test using the independent sample t test shows that the p-level is smaller than 0.05 (p 0.05), which is 0.00. The result proves that the jigsaw learning model affects the learning result. In conclusion, the jigsaw learning model affects the learning result of students of SMA Negeri 7 Malang.Based on result above, there are several services for geography teacher, namely; (a) teachers should determine expert team in other learning model; (b) teachers need to give more time for the students to comprehend the materials well. Last for the further research, the researcher could conduct the research with the same variable but different location, level of education and materials. The model should be experimented for subject other than geography in order to assure its usefulness and effectiveness.Penelitian ini mencoba untuk menemukan perbedaan yang signifikan hasil belajar mata pelajaran geografi antara siswa yang dibelajarkan dengan model pembelajaran jigsaw dan yang dibelajarkan dengan model penjelasan dan diskusi guru. Hipotesis dalam penelitian ini adalah terdapat perbedaan yang signifikan antara hasil belajar siswa yang dibelajarkan dengan model pembelajaran jigsaw dan siswa yang dibelajarkan dengan model penjelasan dan diskusi guru. Penelitian ini menerapkan pendekatan eksperimen semu dengan Non Equivalent Control Group Design. Variabel terikat adalah hasil belajar dan variabel bebasnya adalah model pembelajaran jigsaw. Sebagai instrumen tes essay digunakan untuk menguji hasil belajar siswa. Hasil berupa data kemudian dianalisis menggunakan uji-t dengan SPSS 16.0 for Windows. Rata-rata perolehan skor hasil belajar siswa kelompok eksperimen lebih tinggi dari pada kelompok kontrol yaitu 4,75 dan 2,60. Data hasil uji-t menggunakan independent sample t test menunjukkan bahwa p-level lebih kecil dari 0,05 (p 0,05) yaitu 0,00. Hasil tersebut membuktikan bahwa model pembelajaran jigsaw berpengaruh terhadap hasil belajar. Kesimpulannya, model pembelajaran jigsaw berpengaruh terhadap hasil belajar siswa SMA Negeri 7 Malang. Berdasarkan hasil penelitian di atas, terdapat beberapa layanan bagi guru geografi yaitu; (a) guru harus menentukan tim ahli dalam model pembelajaran lain; (b) guru perlu memberikan lebih banyak waktu bagi siswa untuk memahami materi dengan baik. Terakhir untuk penelitian selanjutnya, peneliti dapat melakukan penelitian dengan variabel yang sama tetapi berbeda lokasi, tingkat pendidikan dan materi. Model harus diujicobakan untuk subjek selain geografi untuk memastikan kegunaan dan efektivitasnya.